CEFPIROME IN GYNECOLOGICAL INFECTIONS - IMAGAWA, NOBUYUKI; ISHIKAWA, TAKUJI; HAYASHI, SHIGEOKI; HAYASHI, MOICHIROH; KAWAKATSU, MASAHIDE; YAMATO, TATSUO (CHEMOTHERAPY, 1991)
We studied the clinical efficacy of cefpirome (CPR) in gynecological infections by treating patients with 0.5-1.0g/day intravenously and obtained the following results. 1. The response to CPR was good in all 13 patients with gynecological infections (endometritis 8, salpingitis 3, Bartholin's gland abscess 2). 2. In a bacteriological study, 9 strains were isolated from 8 cases. All strains were eradicated. 3. There were no side effects or abnormal laboratory findings.